7-3y+6=-7

Simple and best practice solution for 7-3y+6=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-3y+6=-7 equation:


Simplifying
7 + -3y + 6 = -7

Reorder the terms:
7 + 6 + -3y = -7

Combine like terms: 7 + 6 = 13
13 + -3y = -7

Solving
13 + -3y = -7

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + -3y = -7 + -13

Combine like terms: 13 + -13 = 0
0 + -3y = -7 + -13
-3y = -7 + -13

Combine like terms: -7 + -13 = -20
-3y = -20

Divide each side by '-3'.
y = 6.666666667

Simplifying
y = 6.666666667

See similar equations:

| 9=5+2g | | -4(6n-4)-7= | | ax^2-bx^2=0 | | 16+c=-5 | | 1+4a-a= | | 15y+3x=61 | | 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) | | p+(-9)=8 | | 10=3y+1 | | -14-8k=2k+8k | | 3x=x^2+9 | | 50=x(x*0.16) | | -12+5m+10=2m-10-m | | (15/28)/35 | | t/7=-9/1 | | 8r-5q=3forq | | -d+7= | | 13x+1+12x+9= | | t/t=-9/1 | | 10x-4-6x=-84 | | 9x-81=7 | | .3+.6=.06 | | 4/24 | | (-6)(-6)= | | 24/.4 | | 19=3t-23 | | 3(3m+4)-2(m-7)=0 | | 6d-18+2=2 | | 24/.04 | | 12x+12x+16+10x-4=102 |

Equations solver categories